Avaliação dos Efeitos de Fotoprotetores em Organismos Aquáticos - Paula, Vinícius de Carvalho Soares de (2019)
Ultraviolet (UV) filters are molecules used to protect against UVA (320-400 nm) and UVB (280-320 nm) radiation and are present in personal care products such as creams, body lotions and photoprotectors. Due to the low efficiency of sewage collection and treatment systems, aquatic ecosystems are the main destinations of these molecules, being found in ng L-1 to μg L-1. The presence of these substances in the environment is of deleterious effects on aquatic organisms. The aim of this study was to evaluate the effects of 2-ethylhexyl, 4-methoxycinnamate (EHMC), avobenzone (AVO), benzophenone-3 (BF-3) and octocrylene (OC) on aquatic organisms of different trophic levels through acute and chronic exposures. Considering these factors, it was initially evaluated the acute (Artemia salina; Daphnia magna) and chronic (Desmodesmus subspicatus; Daphnia magna) toxicity for CENO and ecological risk quotient. Afterwards, toxicity tests were performed considering concentrations of environmental relevance, exposing embryos of Rhamdia quelen, two consecutive generations of Daphnia magna and subsequent evaluation of multiple biochemical biomarkers (acetylcholinesterase - AChE, catalase - CAT, glutathione-S-transferase - GST, superoxide dismutase - SOD, protein carbonylation - PCO). In the initial analyzes, EHMC showed to be the most toxic for all the organisms tested (Desmodesmus subspicatus: EC50 = 0.37 mg L-1, CENO = 0.05 mg L-1, Artemia saline EC50 = 0.37 mg L-1; Daphnia magna EC50 = 0.50 mg L-1, CENO = 0.009 mg L-1) and although it presented high toxicity, it was considered without ecological risk, according to the application of mathematical estimation by the risk quotient method. However, in the multigenerational studies with Daphnia magna, reproductive delays were observed in the second generation exposed with AVO 4450 ng L-1, BF-3 175 ng L-1 and MIX (mixture of the four molecules), as well as decrease in reproduction rates with AVO, BF-3, EHMC 224 ng L-1 and MIX, besides induction of CAT activity, evidencing an antioxidante system response caused by AVO and BF- 3. The embryos of Rhamdia quelen showed four photoprotectors and their mixture, also significant index of malformations caused by exposure to AVO, EHMC, OC and carbonylated was concluded that the exposure of aquatic organisms to UV filters, even at environmental concentrations, is harmful and can be detrimental to the life cycle of the species, affecting the embryonic and reproductive development.